Estudos sociais para crianças numa democracia: prescrições didáticas para o ensino de história no Brasil sob o prisma estadunidense (1960-1970) - Soares, Elisiane da Silva (My University, 2021)
This research is dedicated to the study of the Social Studies for Children in a Democracy manual with a focus on its materiality and content. This research is dedicated to the study of the Social Studies for Children in a Democracy with a focus on its materiality and content. This work was originally published in 1956, for John U. Michaelis, Professor of School of Education of Berkeley University, in California. The copy is printed in 1970, with translation of Leonel Vallandro, the 4th printing of the 2nd edition published by Editora Globo. The book presents prescriptions for teachers who wish to ?improve children?s social education? and its central theme is the defense that ?democratic values and behavior must permeate all phases of the social studies program?. In Brazil, the discipline of Social Studies has become required in Basic and Higher Education since 1967 and in 1969, the Social Studies course was implemented in University of Caxias do Sul (UCS), who used the Michaelis manual as a reference. With that, draw attention to the strengthening of political relations between Brazil and The United States, in the sense of implementing the American model in Brazilian education through agreements and covenants with development agencies that guaranteed their spaces at universities. That said, the objective of this work is to analyze the referred manual, in order to perceive American influences in the Brazilian education and the repercussion of movements of renovation of the superior education through the documentation related to the History Course of UCS (University of Caxias do Sul) between the years of 1960 and 1970, available ate the Documentation Center (CEDOC/UCS). For this analysis, anchoring on the theoretical assumptions of Cultural History, given its importance for the analysis of the processes where a meaning is built, we rely on Chartier (1990) and Pesavento (2003). As teacher training and curriculum structure García (1999) and Goodson (1995), were important authors to direct this research. The methodology of documentary research and content analysis was supported by Chevel (1990), Bardin (1977), Bauer and Gaskell (2002) and Galiazzi and Moraes (2007), observing the contributions and paths taken by the authors in their research fields. From the analysis of the documents and the study of the work, we recognize that the relations observer in the period and the didactic prescriptions foresaw the establishment of a democracy based, and why not say imported, in the United States. Thus, we consider the manual in its breadth, as a cultural introjection of what is desired of a history teacher who is recognized until today.
Esta pesquisa se dedica ao estudo do manual Estudos Sociais para crianças numa democracia com enfoque em sua materialidade e conteúdo. A obra foi originalmente publicada em 1956, por John U. Michaelis, Professor da Escola de Educação da Universidade de Berkeley, Califórnia. O exemplar tem sua impressão em 1970, com tradução de Leonel Vallandro, sendo a 4ª impressão da 2ª edição publicada pela Editora Globo. O livro apresenta prescrições aos professores que desejam ?melhorar a educação social das crianças? e o seu tema central é a defesa de que ?os valores e o comportamento democráticos devem impregnar todas as fases do programa de estudos sociais?. No Brasil, a disciplina de Estudos Sociais tornou-se obrigatória no Ensino Básico e Superior a partir de 1967 e em 1969, foi, então, implantado o curso de Estudos Sociais na Universidade de Caxias do Sul (UCS), que utilizou o manual de Michaelis como referência. Com isso, destacamos o fortalecimento das relações políticas entre Brasil e Estados Unidos, no sentido de implementar o modelo estadunidense na educação brasileira por meio de acordos e convênios com agências de fomento que garantiram seus espaços nas universidades. Dito isso, o objetivo deste trabalho é analisar o referido manual, a fim de perceber influências estadunidenses na educação brasileira e a repercussão de movimentos de renovação do ensino superior através da documentação relacionada ao Curso de História da UCS entre os anos de 1960 e 1970, disponíveis no Centro de Documentação (CEDOC/UCS). Para essa análise, ancorando-se nos pressupostos teóricos da História Cultural, visto a sua importância para a análise dos processos onde um sentido é construído, apoiamo-nos em Chartier (1990) e Pesavento (2003). Quanto a formação de professores e estrutura curricular, García (1999) e Goodson (1995), foram autores importantes para direcionar essa pesquisa. A metodologia de pesquisa documental e análise de conteúdo foi amparada em Chervel (1990), Bardin (1977), Bauer e Gaskell (2002) e Moraes e Galiazzi (2007), observando as contribuições e os trilhos tomados pelos autores em seus campos de pesquisas. A partir das análises dos documentos e do estudo da obra, reconhecemos que, as relações observadas no período e as prescrições didáticas, previam a instauração de uma democracia baseada, e por que não dizer importada, nos Estados Unidos. Dessa forma, consideramos o manual, em sua amplitude, como uma introjeção cultural do que se deseja de um professor de história que se reconhece até a atualidade.
Keywords: Ciências sociais; Democracia; Didática; História - Estudo e ensino; Professores - Formação; Social sciences; Democracy; Didatics; History - Study and teaching; Teachers, Training of